Racialization of peer‐to‐peer transactions: Inequality and barriers to legitimacy. Issue 2 (11th November 2020) - Shepherd, Steven; Matherly, Ted
Abstract: Racial disparities exist in how different peer‐to‐peer (P2P) business activities are treated. Adapting from institutional theory, whiteness theory, and stereotyping research, we find across a series of experiments that P2P activities are rated more negatively and lower in normative legitimacy when their actors are perceived to be Black as opposed to White. Local acceptance and regulative legitimacy increased normative legitimacy ratings for P2P activities in a Black community, but did not erase the normative legitimacy gap. Moreover, we find that popular terms for P2P businesses ("sharing economy" and "side hustle") have racial associations, influencing perceptions of normative legitimacy. However, we also show that this may potentially be altered by the legitimating action (an advertising campaign) of a major P2P company employing these terms. Our results suggest that policymakers and programs for improving entrepreneurial achievement need to explicitly consider these racial associations and perceived differences in legitimacy.